(untitled) (Inženierzinātņu un augstskolu vēsture, 2018)
Ilona Dumpe (1891–1962) ieguva mājskolotājas tiesības, taču izvēlējās kancelejas darbinieces darbu. Viņa ir trešā sieviete Rīgas Politehniskā institūta (RPI) kancelejā un sāka tajā strādāt 1913. gadā. 1916. gadā viņa sāka strādāt fabrikā «Provodņik». 1919. gada februārī I. Dumpe atkal atgriezās augstskolā, uz RPI bāzes izveidotajā padomju Latvijas Augstskolā, pēc tam turpināja darbu dažādos amatos Latvijas Universitātē līdz 1944. gada augustam, kad devās emigrācijā. Par darbu saņēmusi valsts apbalvojumus. Mūža nogali pavadījusi Vācijā, tulkojusi latviešu rakstnieku darbus vācu valodā. The life and work of Ilona Dumpe (1891–1962) ‒ an Employee of Riga Polytechnic Institute and of the University of Latvia Ilona Dumpe (born Stern; after adoption − Krieviņa) was raised as a single child in a step-family. She got married, but her husband died quite early and she had to take care of his relatives. She received the education of a house teacher, but decided to apply for a post at the Chancellery of Riga Polytechnic Institute (RPI) where she worked from 1913 to 1916. When RPI was founded, there were no female students, no female academic staff or female employees. In 1913, Ilona Dumpe was only the third woman employed at the Chancellery of RPI. Emancipation of women made its first steps. Until 1917, RPI had only male students and male teachers. When RPI was evacuated by the tsarist administration to Moscow, Ilona Dumpe moved to Moscow where she worked from 1916 to 1918 at the factory «Prowodnik» which had been evacuated to Moscow as well. When in 1919, RPI was dissolved and the Institution of Higher Education of Latvia was founded in the buildings of the defunct RPI she started to work there. In 1992, after the institution was renamed into the University of Latvia she took three different positions: in the archives, as a translator and as a typist. She received awards of the Government of Latvia for her skillful work. In 1944, at the end of World War II she immigrated to Germany like many Latvians. In Germany, she worked at the Baltic University from 1946 to 1949 and at the Baltic Research Institute in Bonn (Germany) founded in 1953. She has translated a number of works by Latvian writers. Ilona Dumpe died in 1962. Keywords: Ilona Dumpe, Riga Polytechnic Institute, Chancellery of the University of Latvia. Жизненный путь и трудовая деятельность сотрудницы Рижского политехнического института и Латвийского университета Илоны Думпе (1891–1962) Илона Думпе (она же Штерн, Криевиня; 1891–1962) выросла единственным ребенком в приемной семье. Позже вышла замуж, но муж вскоре умер. Приходилось заботиться об одиноких родственниках. И. Думпе получила права домашней учительницы, но выбрала работу в канцелярии. Стала третьей женщиной в канцелярии Рижского политехнического института, поступив туда на работу в 1913 году. С 1916 по 1918 год трудилась на эвакуированном в Москву заводе «Проводник». С 1919 года – вновь в системе высшего образования – в Латвийском университете (до 1922 года – Высшая школа Латвии), где исполняла обязанности архивариуса, секретаря и переводчицы. Ее работу отмечали в том числе правительственными наградами. В августе 1944 года вышла в отставку и отправилась в изгнание. Остаток жизни провела в Германии, где работала секретарем в Балтийском университете (1946–1949), потом в Балтийском исследовательском институте. Переводила на немецкий язык труды латышских писателей, таким образом пропагандируя латышскую культуру за границей. Скончалась в 1962 году недалеко от Бонна в возрасте семидесяти лет. Ключевые слова: Илона Думпе, Рижский политехнический институт, канцелярия ЛУ.